Implementation of Database Distributed Sharding Horizontal Partition in MySQL. Case Study of Application of Food Serving On Kemkes - Samidi Samidi; Ronal Yulyanto Suladi; Ario Bambang Lesmana (JURNAL SISFOTEK GLOBAL, 2022)
In today's digital era, database systems are becoming a mandatory thing that is used in every industry field to improve the performance of the industry, over time with the increasing need for databases, single databases and single servers are considered less capable in handling data that continues to increase in number, so it often leads to a decline in performance. Therefore came the idea of centralized data storage that can be modified to accommodate the availability, scalability, reliability, and management of data. One way that can be done is to apply Distribute Database using Sharding Horizontal Partition technique and experimental methods using mariadb and spider engine. The test was carried out on the database of food processing sites (TPP) in the TPP application at the ministry of health. The test results prove that although in some journals about Sharding, more sharding is implemented on NoSQL DBMS such as MongoDB, influx dB. In this study it can be proven that sharding can also be done in relational DBMS such as MariaDB and MySQL, data can be distribute and load process too, test result successful although the performance of time query response is still better single database than distribute database.